2022
DOI: 10.21580/pjpp.v7i2.10637
|View full text |Cite
|
Sign up to set email alerts
|

Social media pressure and the body dysmorphic disorder tendency in women: The mediating role of perfectionism

Abstract: The ideal body image displayed in social media often makes women vulnerable to body image issues, one of which is body dysmorphic disorder (BDD). This study aims to examine the role of social media pressure in predicting the tendency towards such a disorder in emerging adult women, with each of the three dimensions of perfectionism as a mediator. The participants were 385 women aged 18-25 years who used social media and were selected using the convenience sampling technique. Data were collected using the Body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This finding is consistent with previous research showing that that self-oriented, but not socially-prescribed, perfectionism is a risk factor for body dysmorphic symptoms ( Krebs et al, 2019 ). Furthermore, discrepancy perfectionism, occurring when there is excessive focus on the discrepancy between one’s standards for oneself and one’s actual performance ( Slaney et al, 2001 ), has been found to mediate the path between social media pressure and body dysmorphic symptoms ( Sulistyo et al, 2022 ). Taken together, the findings of these studies raise the possibility that individuals with higher levels of self-oriented perfectionism are more likely to compare themselves with idealised images of beauty and to become self-critical if they perceive their own appearance as falling short of these standards, which in turns fuels body dysmorphic symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous research showing that that self-oriented, but not socially-prescribed, perfectionism is a risk factor for body dysmorphic symptoms ( Krebs et al, 2019 ). Furthermore, discrepancy perfectionism, occurring when there is excessive focus on the discrepancy between one’s standards for oneself and one’s actual performance ( Slaney et al, 2001 ), has been found to mediate the path between social media pressure and body dysmorphic symptoms ( Sulistyo et al, 2022 ). Taken together, the findings of these studies raise the possibility that individuals with higher levels of self-oriented perfectionism are more likely to compare themselves with idealised images of beauty and to become self-critical if they perceive their own appearance as falling short of these standards, which in turns fuels body dysmorphic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, existing research has shown that socially-prescribed perfectionism is associated with body dysmorphic symptoms amongst university students ( Hanstock and O'Mahony, 2002 ; Bartsch, 2007 ) and that self-oriented perfectionism predicts body dysmorphic symptoms over time ( Krebs et al, 2019 ). Additionally, newer findings indicate that perfectionism mediates the association between social media pressure felt by young adult women and body dysmorphic symptoms ( Sulistyo et al, 2022 ). It is therefore possible that perfectionism also plays a moderating role in the association between SMU and body dysmorphic symptoms, particularly when exposed to image-based content.…”
Section: Introductionmentioning
confidence: 99%